2006
DOI: 10.1007/s00264-005-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation after one-stage anterior cruciate reconstruction and osteochondral grafting

Abstract: At least 10-20% of all ACL reconstructions require additional cartilage repair. The aim of this study was to compare the activity recovered by patients after one-stage open ACL reconstruction and osteochondral autologous grafting of articular cartilage lesions and after isolated open ACL reconstruction. The study group included 21 patients with chronic ACL deficiency and grade III or IV cartilage lesion according to the ICRS scale who were treated with combined ACL reconstruction and osteochondral grafting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Concomitant drilling, MF, periosteal flap, OAT, and ACI of cartilage lesions and ACL reconstruction have shown acceptable and promising results in the previous literature. 1,2,6,17,23,25,29,30 However, these studies have been case series or case-control studies with relatively small numbers of patients included in the different treatment groups, making it difficult to conclude and generalize about the treatment of choice. The only randomized trial on the concomitant treatment of cartilage lesions and ACL reconstruction is a recent study by Gudas et al, 21 which compared patients undergoing debridement, MF, and OAT of concomitant cartilage lesions at 3-year follow-up after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant drilling, MF, periosteal flap, OAT, and ACI of cartilage lesions and ACL reconstruction have shown acceptable and promising results in the previous literature. 1,2,6,17,23,25,29,30 However, these studies have been case series or case-control studies with relatively small numbers of patients included in the different treatment groups, making it difficult to conclude and generalize about the treatment of choice. The only randomized trial on the concomitant treatment of cartilage lesions and ACL reconstruction is a recent study by Gudas et al, 21 which compared patients undergoing debridement, MF, and OAT of concomitant cartilage lesions at 3-year follow-up after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The use of postoperative continuous passive motion was reported in three studies [8, 10, 23]. However, the details describing the duration of use was only listed in one study by Alfredson et al [8], where it was used for 7 days; this period included an epidural for the first 5 days to facilitate pain‐free motion.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the only two available comparative studies confirmed the results already known from the cartilage literature: OAT provides a better tissue and clinical outcome with respect to bone marrow stimulation, especially for mid‐sized lesions [30, 46], thus underlining the importance of the treatment strategy chosen to address cartilage lesions. Nonetheless, beside sporadic reports suggest the usefulness of different procedures [26, 29, 67], an overall poorer outcome with respect to that of patients without lesions of the articular surface has been documented regardless of cartilage treatments [26, 29]. Further studies should focus on optimizing the treatment of cartilage lesions found during ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%